THE PROBLEM OF OPTIMIZATION OF EXPENSES OF AN ENTERPRISE IN CRISIS CONDITIONS - T. Barsova; A. Putyatin; O. Orlova (Вестник университета)
The article examines the main factors that influencе on the costs of enterprise. Various types of classification of expense are analyzed: internal and external, planned and accidental, primary and secondary. A comprehensive approach to the analysis of the possibility of reducing the costs for cost of goods describes.